Analisis Kemampuan Mahasiswa PGSD dalam Menerima Mata Kuliah Matematika Dasar Berbasis STEM di Surakarta - Indah Werdiningsih; Larassati Larassati; Muhamad Ali Gufron (ALSYS, 2026)
This study was motivated by the limited research on the ability of Elementary School Teacher Education (PGSD) students to receive STEM-based basic mathematics learning, although this approach is considered to play an important role in developing 21st-century skills in higher education. This study aims to describe the ability of PGSD students to receive STEM-based basic mathematics courses in Surakarta. This study employed a qualitative approach with a descriptive design. The research participants were students of the PGSD Study Program in Surakarta selected through purposive sampling. Data were collected through interviews, observation, documentation, and open-ended questionnaires and were then analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results showed that students had a fairly good ability to receive STEM-based basic mathematics learning. Students were able to understand the relationship between mathematical concepts, science, technology, and contextual problem-solving, and they showed strong interest in project-based collaborative learning. Nevertheless, there were still obstacles in technology integration and the application of simple engineering aspects. These findings are in line with constructivist theory and contextual learning, which emphasize the importance of active learning experiences in building conceptual understanding. The conclusion of this study affirms that STEM-based basic mathematics learning can provide more meaningful learning experiences and support the strengthening of critical thinking, communication, collaboration, and creativity skills among PGSD students. The implications of this study include theoretical contributions to the development of STEM learning literature in the context of elementary school teacher education and practical implications for lecturers and curriculum developers in designing more innovative learning integrated with technology. This study also opens opportunities for further research on the development of digital technology-based STEM learning models and the influence of self-efficacy on students’ readiness to participate in STEM learning.